2013
DOI: 10.1371/journal.pone.0054119
|View full text |Cite
|
Sign up to set email alerts
|

A C-Repeat Binding Factor Transcriptional Activator (CBF/DREB1) from European Bilberry (Vaccinium myrtillus) Induces Freezing Tolerance When Expressed in Arabidopsis thaliana

Abstract: Freezing stress affects all plants from temperate zones to the poles. Global climate change means such freezing events are becoming less predictable. This in turn reduces the ability of plants to predict the approaching low temperatures and cold acclimate. This has consequences for crop yields and distribution of wild plant species. C-repeat binding factors (CBFs) are transcription factors previously shown to play a vital role in the acclimation process of Arabidopsis thaliana, controlling the expression of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The amino acid change is also found in CBF4 from A. thaliana, HbCBF1 from H. brasiliensis, CBFs from Vaccinium myrtillus. It has been previously demonstrated that the change in V. myrtillus CBFs do not inhibit the binding of CBF to the DRE/CRT DNA motif (Polashock et al 2010;Walworth et al 2012;Oakenfull et al 2013). Therefore, the change in cassava MeCBF1 may not inhibit its function.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The amino acid change is also found in CBF4 from A. thaliana, HbCBF1 from H. brasiliensis, CBFs from Vaccinium myrtillus. It has been previously demonstrated that the change in V. myrtillus CBFs do not inhibit the binding of CBF to the DRE/CRT DNA motif (Polashock et al 2010;Walworth et al 2012;Oakenfull et al 2013). Therefore, the change in cassava MeCBF1 may not inhibit its function.…”
Section: Resultsmentioning
confidence: 98%
“…The deduced amino acid sequence of MeCBF1 is 231 amino acids, and contains motifs of PKK(P/R)AGRxKFxETRHP and DSxWR (Fig. 1), which are commonly conserved in C-repeat binding factor transcriptional activator genes (Canella et al 2010;He et al 2012;Oakenfull et al 2013;Peng et al 2013). The molecular weight (MW) and theoretical isoelectric point (PI) were 25.572 kDa and 5.36, respectively, which were calculated by the online Computer PI/Mw Tool (http://cn.expasy.org/tool).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of OsDREB1A (Dubouzet et al 2003 ), maize DREB1 (Qin et al 2004 ), a modifi ed AP2/ERF transcription factor from Brassica napus (Xiong et al 2013 ), Vaccinium myrtillus CBF/DREB1 (Oakenfull et al 2013 ) in transgenic Arabidopsis plants resulted in enhanced freezing tolerance. Transgenic barley lines overexpressing TaCBF14 and TaCBF15 exhibited enhanced freezing tolerance (Soltesz et al 2013 ).…”
Section: Cbf/dreb-responsive Pathwaymentioning
confidence: 99%
“…Cold-inducible DREB1/CBF genes have been isolated from numerous dicotyledonous plant species, such as oilseed rape, Vaccinium myrtillus (Oakenfull et al , 2013), Caragana korshinskii (Wang et al , 2011), Capsicum annuum (Hong and Kim, 2005), grape (Xiao et al , 2006), and chrysanthemum (Tong et al. , 2009), as well as monocotylous plant species, such as wheat ( Triticum aestivum ), rye ( Secale cereale ) (Jaglo et al , 2001), rice (Dubouzet et al , 2003), maize (Qin et al , 2004), etc.…”
Section: Introductionmentioning
confidence: 99%